EFL Students’ Perceptions Toward Online English Learning during the Covid-19 Outbreak - Albiansyah Albiansyah; Didin Nuruddin Hidayat; Rino Dedi Aringga (Universitas Muhammadiyah Jember, 2021)
The present study aims at investigating English Foreign Language Students’ perceptions toward online English learning at a private vocational school, Sekolah Menengah Kejuruan Bina Informatika Bintaro. In order to answer the research question, this study occupied descriptive qualitative research. The data were collected through questionnaires which were distributed to students. The participants of this study were 54 vocational high school students on 2020/2021 academic year who attended online English learning in the second semester. The samples were chosen by implementing purposive sampling technique. The results of the perception of most participants in the study expressed their support for the conduct of online English learning during the Covid-19 pandemic and agreed with the ease of accessibility. However, the study revealed some disagreement in terms of ease of use of the tools, English learning material understanding, and interaction. Further, the results of the research showed 60% of students stated that online English learning was unattractive compared to face-to-face learning, 27% said it was still interesting, and the rest were hesitant. Furthermore, it is hoped that English teachers use more suitable platforms when teaching English in online learning, so that students will be more interested in learning English online and will gain optimal learning outcomes.